Module type industrial information security remote measurement and control terminal - WU DONGBO; GUAN CHENGGONG; ZHANG XIAOXU (2016)
The invention discloses a module type industrial information security remote measurement and control terminal which comprises a module shell, a control board, a left terminal baffle plate, a right terminal baffle plate and fixed screws. The module shell is a trapezoid body, and the control board is fixed through the internal clamping groove of the trapezoid body. Two end faces of the module shell are fixedly connected to the left terminal baffle plate and the right terminal baffle plate through the fixed screws. The left terminal baffle plate is provided with an RS-485 interface module and an alarm module output interface, and the right terminal baffle plate is provided with an Ethernet communication module interface, an RS232 module interface, a signal module indication lamp and a dual-power-supply power supply module interface. The control board comprises a dual-power-supply power supply module, an MCU processor module, a data storage module, an Ethernet communication module, an SM encryption/decryption mod